Insights on the molecular mechanism of neuroprotection exerted by edible bird’s nest and its bioactive constituents - Weiyi Chu; Chia Wei Phan; Seng Joe Lim; Abdul Salam Babji (Food Science and Human Wellness)
Neurodegenerative diseases are often associated with the accumulation of oxidative stress and neuroinflammation. Edible bird’s nest (EBN) is a glycoprotein (sialylated mucin glycopeptides) found to be beneficial against neurodegenerative diseases. Antioxidative, anti-inflammatory, and anti-apoptotic properties of EBN in preserving neuronal cells were widely researched using in vitro and in vivo models. Functional effects of EBN are often linked to its great number of antioxidants and anti-inflammatory glycopeptides. Bioactive compounds in EBN, especially sialic acid, add value to neurotrophic potential of EBN and contribute to neuronal repair and protection. Various studies reporting the neuroprotective effects of EBN, their molecular mechanisms, and neuroactive composition were gathered in this review to provide better insights on the neuroprotective effects of EBN.